2021
DOI: 10.1007/s00170-021-08407-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and simulation based on mesoscopic model of SiCp/Al composites during precision machining: deformation mechanism and surface quality

Abstract: Ceramic particle-reinforced metal matrix composites (PRMMCs) have been widely applied in modern industry with excellent mechanical characteristics. Meanwhile, the addition of high hardness reinforcements also produces a significant challenge for precision machining of PRMMCs and leads to poor machinability and higher time consumed in the subsequent surface treatment process. To investigate the machining mechanism of PRMMCs, a 2D mesoscopic-based finite element (FE) model reinforced with randomly distributed po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It is believed that when processing SiCp/Al composite materials, SiC is removed through methods, such as crushing, debonding, fracture, shearing, pulling in, and pulling out. Zhou et al [ 11 ] proposed a deformation mechanism and surface quality finite element model that accurately predicted metal matrix composites (MMCs). They found that serrated chips mainly form along the shear plane, accompanied by the generation and propagation of microcracks.…”
Section: Machining Mechanism Of Sicp/almentioning
confidence: 99%
“…It is believed that when processing SiCp/Al composite materials, SiC is removed through methods, such as crushing, debonding, fracture, shearing, pulling in, and pulling out. Zhou et al [ 11 ] proposed a deformation mechanism and surface quality finite element model that accurately predicted metal matrix composites (MMCs). They found that serrated chips mainly form along the shear plane, accompanied by the generation and propagation of microcracks.…”
Section: Machining Mechanism Of Sicp/almentioning
confidence: 99%
“…For instance, the application of materials is inseparable from mechanical processing, which typically involves precise cutting. The quality of the machined surface constitutes a crucial factor that impacts the actual properties of the material [ 8 ]. With the help of finite element simulation, the cutting model of PRMMCs can be established, and the stress-strain relationship, damage form and dynamic chip formation mechanism inside the material during cutting can be simulated from a microscopic perspective [ 9 , 10 ], so as to optimize the processing technology and improve the processing quality.…”
Section: Introductionmentioning
confidence: 99%
“…Cutting parameters have a great influence on the removal form of particles and the quality of the machined surfaces, so many scholars take cutting parameters as the research point. Zhou et al [11] predicted through the finite element model that the increase in cutting depth also increased the probability of particle fracture and debonding under the cutting path, *bradywang@hit.edu.cn; tele 0451-86415244; fax 0451-86415244 thus leading to the deterioration of surface quality. Diptikanta Das et al [12] believed that the setting of cutting depth and cutting speed seriously affects the quality of the machined surface.…”
Section: Introductionmentioning
confidence: 99%